2016
DOI: 10.1080/10400435.2016.1220994
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of wheelchair sitting posture measures using Coach’s Eye in abled subjects

Abstract: People in wheelchairs spend a long time in the sitting position and often incur alignment problems resulting in neck and back pain. This study: (1) assessed the validity/reliability of Coach's Eye (CE) smart device application, (2) examined the effect of seat to back support angle adjustments on head, neck, and shoulder posture in the sitting position, and (3) compared changes in cervical rotation at each back support angle. Abled subjects sat in a wheelchair with back support angles positioned at 90°, 100°, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…According to previous studies, ImageJ has been measured for posture assessment, wheelchair sitting posture, and brow position measurements. [16][17][18] To measure the degree of sagittal spinal postural alignment, the craniovertebral angle in supine (CVAS) and craniohorizontal angle in supine (CHAS) biomarkers were calculated from the images acquired in ImageJ. Previous studies have reported that standing CVA is an index of the anterior tilt of the head, and standing CHA reflects the position and visual field of the upper cervical spine that are associated with good intra-and interrater reliability in standing measurements ( Figure 2).…”
Section: Measurement Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous studies, ImageJ has been measured for posture assessment, wheelchair sitting posture, and brow position measurements. [16][17][18] To measure the degree of sagittal spinal postural alignment, the craniovertebral angle in supine (CVAS) and craniohorizontal angle in supine (CHAS) biomarkers were calculated from the images acquired in ImageJ. Previous studies have reported that standing CVA is an index of the anterior tilt of the head, and standing CHA reflects the position and visual field of the upper cervical spine that are associated with good intra-and interrater reliability in standing measurements ( Figure 2).…”
Section: Measurement Methodsmentioning
confidence: 99%
“…According to previous studies, ImageJ has been measured for posture assessment, wheelchair sitting posture, and brow position measurements. 16 18…”
Section: Methodsmentioning
confidence: 99%
“…The images were captured on a PC, and two angles were calculated for ADS screening using ImageJ (version 1.52, National Institutes of Health, Bethesda, MD, USA). According to previous studies, ImageJ has been used for posture assessment, wheelchair sitting posture, and brow position measurements [18][19][20]. Landmarks for ADS screening were placed on both the lateral canthus and trapezius muscles using the ImageJ point tool.…”
Section: Coronal Spinal Postural Alignment Measurement Using Digital mentioning
confidence: 99%